2013
DOI: 10.1136/bcr-2013-201215
|View full text |Cite
|
Sign up to set email alerts
|

Phalangeal lytic lesion: do not forget osseous sarcoidosis

Abstract: Sarcoidosis is a systemic granulomatous disease that most commonly involves the lung and thoracic lymph nodes. However, any organ can be affected. Osseous sarcoidosis has been reported in 3–13% of the cases. The skeletal involvement on radiographs is usually seen late in the course of the disease and is rarely the initial manifestation. We report a case of sarcoidosis revealed by a lytic lesion of the phalanx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, 2 recent studies identified axial bone involvement with the spine as most commonly affected site followed by the pelvis and hand in third position. Nail and bone involvement are rarely a presenting feature and are both regarded as part of a systemic chronic sarcoidosis as it occurs mainly in young patients with generalized advanced disease, typically with lung involvement, chronic skin lesion, mainly lupus pernio-like lesions and dactylitis or both [18]. Our patient did not show any other skin lesions nor systemic involvement.…”
Section: Discussionmentioning
confidence: 75%
“…However, 2 recent studies identified axial bone involvement with the spine as most commonly affected site followed by the pelvis and hand in third position. Nail and bone involvement are rarely a presenting feature and are both regarded as part of a systemic chronic sarcoidosis as it occurs mainly in young patients with generalized advanced disease, typically with lung involvement, chronic skin lesion, mainly lupus pernio-like lesions and dactylitis or both [18]. Our patient did not show any other skin lesions nor systemic involvement.…”
Section: Discussionmentioning
confidence: 75%
“…Regardless, this atypical presentation may suggest a link between SLE and rhabdomyolysis that is not yet well described in the current literature. In addition to this rarely described connection between rhabdomyolysis and SLE, others have reported an association between rhabdomyolysis and Sjogren’s syndrome [ 9 – 11 ]. However, the current literature does not describe the incidence of rhabdomyolysis secondary to or concurrent with rheumatic diseases.…”
Section: Discussionmentioning
confidence: 99%